Functional characterization of candidate Persea americana nucleotide-binding leucine rich repeat (PaNLR) genes during Phytophthora cinnamomi infection - Van den Berg, Noelani (University of Pretoria, 2025)
Dissertation (MSc (Genetics))--University of Pretoria, 2024.